Drug Utilization Trends In ENT Out Patient Department In A Teaching Hospital - YADAV PRAMILA,; KANASE VANITA,; LACCHIRAMKA PREETY,; JAIN SIDDHARTH, (International Journal of Pharma and Bio Sciences, 2010)
The primary aim of this study was to generate up to date information on drug use in the ENT outpatient service of our hospital, indications for use, and aptness of its use. A total of 102 prescriptions were randomly audited at varying time interval from the department of ENT during a four month period. The data was collected in customized Performa. The ENT OPD patients constituted 102 (3.42%) of the total patients attending the hospital OPD between the period of June 08 to Sept 08. Maximum cases were of otitis media 21(20.51%), wax 19 (18.62%), tonsillitis16 (15.68%), infective rhinitis 15(14.7%). The average number of drugs used in the prescriptions was 3.28%. None of the drugs were prescribed by generic name. All of them were prescribed with trade names. The topical preparations were the most commonly prescribed drugs. The use of Fixed drug combinations was 75.49%. The average cost per prescription was 105.There was no generic prescribing. Educational sessions for the doctors at different levels to encourage prescribing by generic names and on correct writing of prescriptions may be considered. Studies covering a larger number of patients and for a longer time period are required. A greater number of patients can be studied, seasonal variations can be overcome and drug utilization can be measured quantitatively.